AIAA SPACE 2013 Conference and Exposition 2013
DOI: 10.2514/6.2013-5383
|View full text |Cite
|
Sign up to set email alerts
|

Helicopter Flight Test of a Compact, Real-Time 3-D Flash Lidar for Imaging Hazardous Terrain during Planetary Landing

Abstract: A second generation, compact, real-time, air-cooled 3-D imaging Flash Lidar sensor system, developed from a number of cutting-edge components from industry and NASA, is lab characterized and helicopter flight tested under the Autonomous Precision Landing and Hazard Detection and Avoidance Technology (ALHAT) project. The ALHAT project is seeking to develop a guidance, navigation, and control (GN&C) and sensing system based on lidar technology capable of enabling safe, precise crewed or robotic landings in chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Data from FT5 showed that it was possible to visually identify a hazard smaller than the 40 cm requirement (25 cm hazard height in FT5) even with a GSD worse that the 10 cm requirement and a range precision worse than the current 8 cm. 11 Thus data from both FT5 and FT6 indicate that the 40cm hazard resolution requirement has been met. Figure 17 and Figure 18 are both DEM's each created from a single Flash Lidar range image.…”
Section: Flight Test Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Data from FT5 showed that it was possible to visually identify a hazard smaller than the 40 cm requirement (25 cm hazard height in FT5) even with a GSD worse that the 10 cm requirement and a range precision worse than the current 8 cm. 11 Thus data from both FT5 and FT6 indicate that the 40cm hazard resolution requirement has been met. Figure 17 and Figure 18 are both DEM's each created from a single Flash Lidar range image.…”
Section: Flight Test Resultsmentioning
confidence: 94%
“…Previous flight testing onboard a UH-1H helicopter to the same KSC hazard field validated the Flash Lidar's maximum operational slant range to be 1,350m. 11 Based upon data from early 2014, the reflectivity at 1.06µm of the hazard field at an incidence angle of zero is 70% which is a contributing factor to the Flash Lidar's ability to exceed its maximum operational range requirement of 750m for a 30% reflective surface. Figure 14 shows the median intensity and median slant range as a function of time for the latter portion of free-flight 15 (FF15).…”
Section: Flight Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The color gradient from top to bottom in the image is due to apparent slope caused by the viewing angle. Past flight testing at KSC onboard a NASA UH-1H helicopter has shown the flash LIDARs maximum operational range to be approximately 1350 m. 15 The minimum operational range of the flash LIDAR is dominated by saturation and defocus. The flash LIDAR incorporates an Automatic Gain Correction (AGC) algorithm which can hold the image intensity within the sensor's dynamic range down to ranges of 150 m. The flash LIDAR receiver lens is set for maximum depth of field in order to provide in-focus images at all ranges above 250 m. As an example of the hazard detection capability of the LIDAR, Fig.…”
Section: A Flash Lidarmentioning
confidence: 99%
“…The operation of the flash lidar was characterized during different stages of its development that included extensive laboratory experiments, dynamic truck tests, and three helicopter and one fixed-wing aircraft flight test campaigns. [21][22][23][24][25] These tests helped the development of the prototype unit and functional demonstration onboard the rocket-powered Morpheus vehicle (Fig. 5).…”
Section: Alhat Demonstration Flight Testsmentioning
confidence: 99%